A comparative study of herpes zoster: adult versus paediatric patients - Mondal, Avijit; Kumar, Piyush; Swathi, G; Dasarathan, Subhash (Journal of Pakistan Association of Dermatologists, 2019)
Background Herpes zoster (HZ) is thought to be a disease of older population and if it presents in younger population, it is usually associated with immunosuppressive conditions like leukemia, lymphoma, organ transplantation, HIV infection and chemotherapy. Â Aims The aims of this study were to find out the relative prevalence of paediatric (less than 18 years) herpes zoster among HZ patients and to compare the demographic and clinical profiles of adult and the paediatric patients suffering from HZ. Â Patients and Methods The study was carried out over a period of twelve months at Dermatology outpatient department of two tertiary care centres of East India and a total of ninety cases of HZ were recruited for the study. The diagnosis was made clinically and the details of history, examination and relevant investigations were recorded in case record form, after getting consent from patient (or guardian in case of paediatric patients). Â Results Ninety herpes zoster (HZ) patients were recruited from Dermatology out-patient departments during study period. The relative prevalence of HZ among OPD population was found to be 2.8/1000 population. Paediatric patients (n=21) contributed 23.33% of total HZ cases. The mean age of presentation was 29.62Â±17.52 years. The most frequently affected site was chest (42.66%) followed by abdomen (31.11 %). Ocular involvement was noted in 5.55% cases. All cases and mothers of paediatric cases were tested for human immunodeficiency virus (HIV) infection, and it came out negative in all patients. Of note, one 11-year-old girl developed HZ three weeks after starting on oral mini-pulse therapy with betamethasone for progressive vitiligo vulgaris and another 6 year old boy, diagnosed as a case of nephrotic syndrome was on oral corticosteroid when presented with HZ. Â Conclusion As opposed to the long standing belief, herpes zoster in younger age does not appears to be a rare entity. Herpes zoster is a relatively mild disease in children in contrast to adults. Also, routine HIV testing in paediatric patients presenting with HZ appears to be unnecessary. Â